2021
DOI: 10.1161/circgen.120.003269
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Accuracy of a Polygenic Risk Score for Postoperative Atrial Fibrillation After Cardiac Surgery

Abstract: Background - Postoperative atrial fibrillation (PoAF) remains a significant risk factor for increased morbidity and mortality after cardiac surgery. The ability to accurately identify patients at risk through clinical risk factors is limited. There is growing evidence that polygenic risk contributes significantly to PoAF, and incorporating measures of genetic risk could enhance prediction. Methods - A retrospective cohort study of 1,047 patients of whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…Furthermore, O'Sullivan et al, studying 530,933 SNVs and Pulit et al studying 934 SNVs, found a link between a higher PRS and a higher risk of stroke in AF patients. Additionally, Kertai et al, investigating 2,746 SNVs, detected an association between a higher PRS and a higher risk of developing AF post cardiac surgery [38][39][40]. Similar to this study, multiple studies have observed the trend of significant association of AF recurrence only with a higher PRS and generally not with the SNVs themselves.…”
Section: Discussion Of Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, O'Sullivan et al, studying 530,933 SNVs and Pulit et al studying 934 SNVs, found a link between a higher PRS and a higher risk of stroke in AF patients. Additionally, Kertai et al, investigating 2,746 SNVs, detected an association between a higher PRS and a higher risk of developing AF post cardiac surgery [38][39][40]. Similar to this study, multiple studies have observed the trend of significant association of AF recurrence only with a higher PRS and generally not with the SNVs themselves.…”
Section: Discussion Of Resultssupporting
confidence: 86%
“…The current consensus is that a PRS should include the maximum number of SNVs possible as the pathogenesis of AF is polygenic and not yet fully understood despite being an area of active research [43]. As such, recent studies have utilized whole-genome sequencing in conjunction with GWAS to permit the calculation of PRS using a far greater number of SNVs [37][38][39][40][44][45][46][47][48]. This has been made possible by the increasing availability of whole-genome sequencing [37,41,42,49].…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Another example of how genetic predisposition could help identify patients at risk for postoperative complications was highlighted by a recent study of patients who underwent cardiac surgery in whom the prediction of postoperative atrial fibrillation (POAF) was much improved by the addition of polygenic risk score (odds ratio, 1.63 per SD increase in PRS [95% CI, 1.41-1.90]). 34 PO-AKI is another frequent complication. Tseng et al 35 enrolled 671 patients prospectively undergoing cardiac surgery patients to design ML-based algorithms logistic regression, support vector machine, random forest, extreme gradient boosting, and ensemble.…”
Section: Implementation Science and Societal Acceptancementioning
confidence: 99%
“…Another example of how genetic predisposition could help identify patients at risk for postoperative complications was highlighted by a recent study of patients who underwent cardiac surgery in whom the prediction of postoperative atrial fibrillation (POAF) was much improved by the addition of polygenic risk score (odds ratio, 1.63 per SD increase in PRS [95% CI, 1.41–1.90]). 34…”
Section: Perioperative Pmmentioning
confidence: 99%
“…Widespread adoption of electronic health record systems coupled with an increasing interest in hospital biobanking systems has spurred research efforts spanning machine-learning and genomics communities[17]. These efforts have produced increasingly accurate imputation (current state) and prediction (future state) of patient phenotypes from medical records [8, 9] and polygenic risk scores [13, 1014], and are already being investigated in translational contexts [1518]. For example, recent work has shown that machine learning can leverage high-dimensional data to aid in the prediction of a multitude of clinical phenotypes including cardiac function and arrhythmia [1921], post-operative complications [8, 9], sepsis [22], breast cancer [11, 23], and prostate cancer [24].…”
Section: Introductionmentioning
confidence: 99%